Kewenangan Mahkamah Konstitusi dalam Menafsir Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Syawaluddin Hanadi (Institut Agama Islam Negeri (IAIN) Bone, 2017)
The Constitutional Court as a judicial institution plays an important role in the enforcement of Indonesian law. The institution authority is to interpret the constitution.In accordance with its function, the institution is able to provide an interpretation, not only the juridical interpretation but also the theological or sociological interpretation, letterlijk (original intent), and historical interpretation. These interpretations are used to assess the presence of the law which is considered contrary to the 1945 Constitution of the Republic of Indonesia